Nuclear accumulation of myocyte muscle LIM protein is regulated by heme oxygenase 1 and correlates with cardiac function in the transition to failure. (5th May 2016) - Paudyal, Anju; Dewan, Sukriti; Ikie, Cindy; Whalley, Benjamin J; de Tombe, Pieter P.; Boateng, Samuel Y.
Abstract : Key points: The present study investigated the mechanism associated with impaired cardiac mechanosensing that leads to heart failure by examining the factors regulating muscle LIM protein subcellular distribution in myocytes. In myocytes, muscle LIM protein subcellular distribution is regulated by cell contractility rather than passive stretch via heme oxygenase‐1 and histone deacetylase signalling. The result of the present study provide new insights into mechanotransduction in cardiac myocytes. Myocyte mechanosensitivity, as indicated by the muscle LIM protein ratio, is also correlated with cardiac function in the transition to failure in a guinea‐pig model of disease. This shows that the loss mechanosensitivity plays an important role during the transition to failure in the heart. The present study provides the first indication that mechanosensing could be modified pharmacologically during the transition to heart failure. Abstract: Impaired mechanosensing leads to heart failure and a decreased ratio of cytoplasmic to nuclear CSRP3/muscle LIM protein (MLP ratio) is associated with a loss of mechanosensitivity. In the present study, we tested whether passive or active stress/strain was important in modulating the MLP ratio and determined whether this correlated with heart function during the transition to failure. We exposed cultured neonatal rat myocytes to a 10% cyclic mechanical stretch at 1 Hz, or electrically paced myocytes at 6.8 V (1 Hz) for 48 h. The MLP ratio decreased by 50% ( P < 0.05, n = 4) only in response to electrical pacing, suggesting impaired mechanosensitivity. Inhibition of contractility with 10 μm blebbistatin resulted in an ∼3‐fold increase in the MLP ratio ( n = 8, P < 0.05), indicating that myocyte contractility regulates nuclear MLP. Inhibition of histone deacetylase (HDAC) signalling with trichostatin A increased nuclear MLP following passive stretch, suggesting that HDACs block MLP nuclear accumulation. Inhibition of heme oxygenase1 (HO‐1) activity with protoporphyrin IX zinc(II) blocked MLP nuclear accumulation. To examine how mechanosensitivity changes during the transition to heart failure, we studied a guinea‐pig model of angiotensin II infusion (400 ng kg –1 min –1 ) over 12 weeks. Using subcellular fractionation, we showed that the MLP ratio increased by 88% ( n = 4, P < 0.01) during compensated hypertrophy but decreased significantly during heart failure ( P < 0.001, n = 4). The MLP ratio correlated significantly with the E / A ratio ( r = 0.71, P < 0.01, n = 12), a clinical measure of diastolic function. These data indicate for the first time that myocyte mechanosensitivity as indicated by the MLP ratio is regulated primarily by myocyte contractility via HO‐1 and HDAC signalling. Key points: The present study investigated the mechanism associated with impaired cardiac mechanosensing that leads to heart failure by examining the factors regulating muscle LIM protein subcellular distribution in myocytes. In myocytes, muscle LIM protein subcellular distribution is regulated by cell contractility rather than passive stretch via heme oxygenase‐1 and histone deacetylase signalling. The result of the present study provide new insights into mechanotransduction in cardiac myocytes. Myocyte mechanosensitivity, as indicated by the muscle LIM protein ratio, is also correlated with cardiac function in the transition to failure in a guinea‐pig model of disease. This shows that the loss mechanosensitivity plays an important role during the transition to failure in the heart. The present study provides the first indication that mechanosensing could be modified pharmacologically during the transition to heart failure.